Nina y Laura - Crisóstomo, Alejo; González, Kattia (Ceibita Films, 2015)
Nina and Laura are a couple whose four year-old son Mateo has just died. Laura moves back to Chile seeking the comfort of her family while Nina, intending to reunite with her shortly, is left to tie up loose ends at home: storing Mateo's things and renting out their house. --